Study on the growth mechanism of the internal oxide layer in 9% Ni cryogenic steel - Du, Hegang; Sun, Haoran; Cai, Minghui; Zuo, Xiurong (Frontiers in Materials, 2023)
The oxidation behavior of Ni-rich layer in internal oxide layer (IOL) in 9% Ni cryogenic steel is investigated at 1150 °C for 0-240 min in air atmosphere. The morphology and phase composition of Ni-rich layer are analyzed with energy dispersive spectroscopy, scanning electron microscopy, metallographic microscopy, X-ray diffraction. The results show that the Ni-rich layer mainly consists of the gray Fe3O4/FeO and the white Ni-Fe particles, with a small amount of the black Fe2SiO4. The morphologies of Ni-Fe particles undergo the following changes with isothermal oxidation time: dot-like → strip-like → net-like, at the same time, layered Ni-Fe particle was formed at about 1/3 of the thickness of Ni-rich layer. Comparing with the dot-like Ni-Fe particle, the net-like and layered Ni-Fe particles provide a fast path for the diffusion of O in Ni-rich layer. Whereas the experimental steel still has a much lower oxidation rate, because of the hinderance of Ni-Fe particles on the out-diffusion of Fe. During oxidation process, Kirkendall effect induces pores/cavities in IOL, which weakens the stability of IOL. In the end, the spalling phenomenon of layered Ni-Fe particle occurs at 1150 °C for 180 min.